2016
DOI: 10.1177/2167479516670642
|View full text |Cite
|
Sign up to set email alerts
|

Pervasively Offside

Abstract: Women remain underrepresented in sport media despite increased opportunities in other facets of sport and journalism. Further, women who have held positions in sport media are often perceived as being less credible than men in the field. In an effort to understand why these perceptions exist, the present study examined the influence of gender-role stereotyping and sexism on perceived sportscaster credibility. Using a posttest-only quasi-experimental design, 544 participants watched a video of a basketball deba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 42 publications
(67 reference statements)
1
13
0
Order By: Relevance
“…In this way, they can directly contact consumers and exert a greater influence [8,9]. Despite being an attractive medium of information, used by journalists to express, disseminate and contrast their own opinion with those from other perspectives, reporters are limited in the content they can diffuse [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, they can directly contact consumers and exert a greater influence [8,9]. Despite being an attractive medium of information, used by journalists to express, disseminate and contrast their own opinion with those from other perspectives, reporters are limited in the content they can diffuse [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research reported an influence of gender-related attitudes of participants on byline biases (e.g., gender-role stereotyping and sexism) (Mudrick et al, 2017). In our study, we employed RWA as a more general measurement to assess respondents’ attitudes towards traditional values.…”
Section: Methodsmentioning
confidence: 99%
“…Studies further found that male sports journalists were rated as more competent (Ordman and Zillmann, 1994) and credible (Luisi et al, 2020; Mudrick et al, 2017) compared to female journalists. We therefore make the following hypothesis:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations